Exploring the Knowledge, Attitudes, and Behaviors Students in a Private High School Medan Students Regarding Sexually Transmitted Infections - Maestro, Prenata; Riyadh Ikhsan (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Sexually transmitted infections (STIs) remain a global public health issue, particularly among adolescents who face heightened risks due to biological, social, and behavioral factors. In Indonesia, STI cases continue to rise despite awareness efforts. A private religious school, offers a unique context for examining STI awareness, yet little research has focused on this population in Medan. Purpose: This study aims to assess STI knowledge, attitudes, and behaviors among private high school students, addressing a critical research gap. Methods: A cross-sectional study was conducted among 68 twelfth-grade students, selected via simple random sampling. Data were gathered through a validated 40-question survey on STI knowledge, attitudes, and behaviors. Data were analyzed using SPSS software, and result are presented in descriptive statistics. Result: Findings showed that 47% of students had moderate STI knowledge, 26.5% high, and 26.5% low. Regarding attitudes, 61.8% were moderate and 38.2% showed strong preventive attitudes. Preventive behaviors were strong in 57.4%, moderate in 33.8%, and poor in 8.8%. Female students displayed higher understanding and more positive attitudes toward STI prevention than males. Conclusion: The study concludes that students of a private high school in Medan possess a moderate understanding of STIs, a generally moderate level of attitude and a high level of preventive behavior.